Urban-rural gaps in the prevalence of hypertension, obesity and diabetes in Malaysia / Govindamal Thangiah - Govindamal , Thangiah (2020)
Rapid economic growth has driven urbanization in developed and developing economies. However, it also created several problems, such as a deterioration in health conditions worldwide and widening of urban-rural and income inequality. A major consequence of urbanization include the rising prevalence of non-communicable diseases, cardiovascular disease (CVD) and its risk factors, such as hypertension, obesity and diabetes. The rapid nutrient and physical activity transition due to urbanization and the peculiar form of economic transformation has impacted the CVD risk factors. Rising urban-rural differences in health profiles and CVD risk factors in both locations over years in Malaysia prompted this research study. This study aims to examine if differences exist between urban and rural hypertension, obesity and diabetes prevalence, and if it is so, to determine their causes. This study also seeks to examine income related hypertension, obesity and diabetes inequalities in urban and rural areas. Unlike most past studies, this study also examines the impact of cumulative lifestyle risk factors (CLRF), (physical activity, diet intake and smoking) on the prevalence of hypertension, obesity and diabetes prevalence in both urban and rural areas. A sample of 7301 Malaysian adults from rural and urban locations in Malaysia who voluntarily enrolled in this community-based health survey from years 2007-2010 were used. Participant’s socioeconomic status (SES), physical activity, diet, smoking status and demographic information were recorded through questionnaires. A non-linear Blinder-Oaxaca decomposition analysis was applied to identify the causes of urban-rural differences in hypertension, obesity and diabetes, concentration index and its decomposition analysis was used to assess the burden of these diseases across the income spectrum and multivariate logistic regression analysis was applied to assess the effect of CLRF on hypertension, obesity and diabetes. Findings from this study suggest that demographic factors and SES are among the main factors that cause the urban-rural differences in obesity and diabetes prevalence. Also, the study showed a higher intensity of income related obesity inequality compared to hypertension and diabetes in urban areas. In rural areas, the intensity of income related obesity inequality was highest followed by diabetes and hypertension. Overall, SES was the main cause of income related hypertension, diabetes and obesity inequalities in urban and rural areas except for income related obesity inequality in rural areas where demographic factors explained most the inequalities. Finally, while the findings of the study showed a significant and positive association between CLRF score and obesity as well as diabetes prevalence in urban areas, CLRF score was insignificantly associated with diabetes, hypertension and obesity prevalence in rural areas. Overall, the results suggest that health policy makers should enhance health-care facilities in rural areas, create more awareness on these diseases among urban population, impose tax on products with high sugar and fat content and tobacco especially in urban areas and to eliminate income related health inequalities, policy makers should consider reducing the prices of healthy products and health related products and services such as gym and more.